Assessing the Relationship Between Environmental, Psychological, Physical and Social Towards the Quality of Life - Md Sakip, Siti Rasidah; Mohd Zukri, Anis Zulaikha; Megat Abdul Rahim, Puteri Rohani (International Journal of Sustainable Construction Engineering and Technology, 2023)
The term quality of life (QoL) has been broadly used in various disciplines to describe the concept of personal well-being beyond the simple economist equation of well-being in relation to income. Quality of life is conceptualised in three aspects: (a) role functioning (difficulties in social, occupational, and interpersonal functioning), (b) life satisfaction and well-being, and (c) socio-material conditions (health cost, health care utilisation and employer cost). However, this paper presents a study that focused on the satisfaction of residents associated with crime and quality of life in their residential area. The study was conducted in three states to the targeted respondents in Petaling Jaya (Selangor), Sentul (Kuala Lumpur), and Johor Bahru Selatan (Johor). The selection of these sites is based on a high crime index from 2011 to 2020. Thus, the objective of this paper is to examine the relationship between environmental, psychological, physical, and social towards the quality of life. This research employed a quantitative approach using a random distribution of questionnaires to respondents at the residential areas that are most likely to experience high crime rates. The preliminary survey involved 51 residents as the respondents from the community. The findings of this study showed that there was a significant and positive relationship, with a medium to strong relationship between the environmental, psychological, physical and social towards the quality of life. Thus, it is hoped the findings of this study will highlight the relationship of these elements which are environmental, psychological, physical, and social towards the quality of life.